Frequency and Pattern of Presentation of Infra-Orbital Nerve Injury in Patients of Zygomatic Bone Fracture - Ayesha Shaukat, Asif Nazir, Wajeeha Chauhdry, Tanveer Ahmad Khan, Asfar Hussain, Muhammad Ibrahim (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: In order to evaluate the frequency and kind of infraorbital nerve injury in zygomatic bone fractures Method: A cross-sectional study was conducted from February 2022 to January 2023 at the Oral and Maxillo-Facial Surgery Department, Nishtar Institute of Dentistry, Multan. Sixty-four zygomatic bone fracture patients were included, meeting inclusion and exclusion criteria after a complete clinical and radiological examination. Clinical neuro-sensory testing (NST) was performed to assess nerve injury. The patient’s demographic data, cause of fracture, presence, and type of nerve injury were collected on a specially designed proforma. The data was analysed using SPSS version 22. Frequencies, percentages, and mean ± standard deviation were taken. Results: Sixty four patients were included with male into female ratio of 4.34:1. There was male predominance. Most common cause of ION injury, in zygomatic bone fractures was RTA (n=13,46.4%) while nerve injury was present in 29 patients (46.77%) of patients. Most common presentation of ION nerve injury was paresthesia n=10,34.5%. Conclusion: Zygomatic bone fracture is the leading cause of infra-orbital nerve injury and its most common presentation is paresthesia. Keywords: infra-orbital nerve (ION) injury, paresthesia, zygomatic bone (ZMC) fracture